2008
DOI: 10.1002/macp.200800137
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Melt Crystallization of PCL‐PEG Diblock Copolymers

et al.

Abstract: ROP of PCL was realized in the presence of mPEG with $\overline M _{\rm n}$ = 5 000, using Zn(La)2 as a catalyst. The resulting diblock copolymers with molar ratios of the CL/EO repeat units from 0.2–5.0 were characterized by DSC, WAXD, SEC, and 1H NMR. Melt crystallization was studied and analyzed with the Avrami equation. The spherulite growth rate G was determined at different crystallization temperatures. The G values were found to range between those of mPEG and PCL homopolymers. The morphology of an isot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 28 publications
2
12
2
Order By: Relevance
“…In the spectra of the copolymers, the diffraction peak of PEG at 19.4° and that of PCL at 21.4° are observed, whereas the peak of PEG at 23.3° overlaps with that of PCL at 23.7°. These findings demonstrate that both the PCL and PEG components are able to crystallize in the copolymers, as reported in the literature . The introduction of the PGA component, which could not crystallize due to its low content, did not affect the crystalline structure of the PCL‐PEG copolymers.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…In the spectra of the copolymers, the diffraction peak of PEG at 19.4° and that of PCL at 21.4° are observed, whereas the peak of PEG at 23.3° overlaps with that of PCL at 23.7°. These findings demonstrate that both the PCL and PEG components are able to crystallize in the copolymers, as reported in the literature . The introduction of the PGA component, which could not crystallize due to its low content, did not affect the crystalline structure of the PCL‐PEG copolymers.…”
Section: Resultssupporting
confidence: 86%
“…These findings demonstrate that both the PCL and PEG components are able to crystallize in the copolymers, as reported in the literature. 14,29 The introduction of the PGA component, which could not crystallize due to its low content, did not affect the crystalline structure of the PCL-PEG copolymers.…”
Section: Characterization Of Copolymersmentioning
confidence: 98%
See 1 more Smart Citation
“…The pattern of pure PCL reveals two diffraction peaks at 2θ = 21.4° and 23.7°, and the patterns of the blend films are similar as that of pure PCL. At the same time, the diffraction peaks of PEG at 2θ around 18.6° and 23.3°39 are hardly observable, indicating that the crystallization of PEG has been restrained in the blend. The peak intensities for PCL diffraction in the blend films are lower than those of pure PCL, implying the lower crystallinity of PCL in the blend film.…”
Section: Resultsmentioning
confidence: 98%
“…It was concluded that PCL crystallizes first, followed by the crystallization of PEG chains between preformed PCL lamellae, resulting in the formation of ordinary single‐circled spherulites having alternating lamellae structures of PEG and PCL. In our previous work,20 a series of copolymers with M n,PEG = 5000, CL/EO = 0.2–5.0 were synthesized. The presence of PCL disfavors the crystallization of PEG and vice versa.…”
Section: Introductionmentioning
confidence: 99%